Adsorptive potentiometric stripping analysis of trace tamoxifen at a glassy carbon electrode - Wang, J.; Cai, X. H.; Fernandes, JR; Ozsoz, M.; Grant, D. H. (Elsevier B.V., 1997)
A highly sensitive adsorptive stripping procedure for trace measurement of the anticancer drug tamoxifen is described. The method is based on controlled adsorptive accumulation of the drug at an electrochemically treated glassy carbon electrode, followed by chronopotentiometric measurement of the surface species. The chronopotentiometric operation effectively addresses the large background contribution inherent to the glassy carbon electrode to yield a detection limit of 4 x 10(-10) M after 4 min preconcentration. The adsorptive stripping response is evaluated with respect to electrode type and conditioning, accumulation potential and lime, stripping current, pH, drug concentration, potential interferences, and other variables. Applicability to urine samples is illustrated. (C) 1997 Elsevier B.V. B.V.
Keywords: tamoxifen; glassy carbon electrode; adsorptive stripping voltammetry; chronopotentiometry